CAMELS Analysis Affect Operation Earning of Cooperative in Thailand - Moolkham, Mongkhol; Uachanachit, Daranee (Journal of Modern Learning Development, 2022)
The purpose of this research was to study financial economic conditions from a 6-dimensional perspective based on financial economic analysis of cooperatives and farmers’ groups by CAMELS Analysis ratios comprised of the 1st dimension, capital adequacy against risk management; the 2nd dimension is asset quality; the 3rd dimension is management capacity; the 4th dimension is earning and liquidity; the 5th dimension is sensitivity and the 6th dimension is business impact that affects the operation earning as measured by the ratios of earnings on equity. An samples used in this research were all 7 types of cooperatives that the Cooperative Auditing Department could examine from the total number of cooperatives. by collecting data from the report on the performance and financial status of the Cooperative Auditing Department and the report The Monetary Policy Committee’s interest rate adjustment (since 2007 through 2020), a total of 98 cooperatives per year were obtained respectively. The statistics used for data analysis were mean, maximum, minimum, and research hypothesis were tested using multiple regression analysis. As a result, it reveals that assets have a positive impact on the operation earnings as measured by the ratios of earning and liquidity as measured by operation expenses to profit ratios which had a statistically significant negative effect on the operation earnings upon investment as measured by the ratios of earnings on significant equity ratios of .05, indicating that if a cooperative uses its operating assets to generate high revenues as well as reduce unnecessary costs and expenses, it will result in a higher operation earnings on equity respectively.